ANALISIS NILAI WTP (WILLINGNESS TO PAY) UNTUK MENENTUKAN NILAI EKONOMI KAWASAN WISATA ALAM DI KABUPATEN SEMARANG BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) (Studi Kasus, Kecamatan Bandungan , Kecamatan Sumowono, Kecamatan Ungaran Barat) - Mega Dwijayanti; Bambang Sudarsono; Andri Suprayogi (Departement Teknik Geodesi Universitas Diponegoro, 2015)
ABSTRACTSemarang districtis geographically located inYogyakarta-Semarang-Solo tourism traffic lane,consists of 19 subdistricts and 235 villages, its location are strategic, it’son the economic growth path across the industrial, agriculture and tourism construction, and it has42 tourism object. The tourist area that are made for the object of research is Umbul Sidomukti, Semirang waterfall, and Seven Angels waterfall, the three of them make the wealth of natural resources as a visited tourism object.This study used aquestionnaire that are derived from BPN with 212 SPT form format for TCM (Travel Cost Method) approach and the 211a form for CVM (Contingent Valuation Method) approach, the information obtained from this form are calculated with a double regression methods that were subsequently used in the calculation of consumer surplus and the willingness to pay on the existence of the regionin order to obtain the total economy value of an area. By using 2010 Quickbird data image and the GPS’s data field coordinates, so the total economic value obtained can be visualized into an Economic Value Zone Map (ZNEK Map), Direct Use Value Map and the Existence Value MaP From the research result, the consumer’s surplus value of Umbul Sidomukti is Rp. 660.501,- million, the value of willingness to pay is Rp. 200.634,- For the Semirang waterfall, the consumer’s surplus value is Rp. 164.350,- the willingness to pay is Rp. 75.801,- and for the Seven Angels waterfall, the consumer’s surplus value is Rp. 780.892,- the willingnessto pay is Rp. 99.150,-. The total economic value obtained over the benefits value from the existence of the regional and the regional economic value based on the travel provider function for the Umbul Sidomukti region is Rp. 29.814.200.280,- Semirang waterfall, Rp. 2.385.280.957,- and the Seven Angels waterfall is Rp. 5.214.848.904,-Kata Kunci : Total economic value, Willingness To Pay, Direct Use Value, Exixtence Value